2022
DOI: 10.52970/grfm.v2i2.175
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Good Corporate Governance and Company Size on Stock Prices in Manufacturing Companies Listed on the Indonesia Stock Exchange

Abstract: This study aims to determine the impact of excellent corporate governance ownership structure on the firm size on stock prices in manufacturing companies listed on the Indonesia Stock Exchange, both simultaneously and partially. According to the findings, good corporate governance, as evaluated by the board of directors and the commissioners, negatively and substantially impacts stock prices. In contrast, the audit committee has a positive and significant impact on stock prices. The natural logarithm of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…One aspect of this impact is the relationship between corporate governance and stock prices. Studies have shown that good corporate governance can have both positive and negative effects on stock prices [1]- [3]. For example, the number of board members and the presence of an audit committee can influence stock prices [1].…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of this impact is the relationship between corporate governance and stock prices. Studies have shown that good corporate governance can have both positive and negative effects on stock prices [1]- [3]. For example, the number of board members and the presence of an audit committee can influence stock prices [1].…”
Section: Introductionmentioning
confidence: 99%